ANALISIS PERUBAHAN PENGGUNAAN LAHAN DAN TINGKAT KERENTANAN SOSIAL EKONOMI DI KAWASAN DANAU MANINJAU - Yudi Antomi (JURUSAN GEOGRAFI FIS UNP, 2020)
ABSTRACT This study aims to calculate and simulate the development of economic values of each type of land use, the level of pollution and analyze the level of socio-economic vulnerability of the nagari community. This study reveals that from the type of land use that shows economic development and a high level of damage is the use of floating net cages (FNC). FNC economic growth in 2014 reached 1.5 trillion rupiah. Judging from the level of socio-economic vulnerability of the nagari community in the Lake Maninjau Region (LMR) it was found that the nagari included as vulnerable were Nagari Tanjung sani, Nagari Sungai Batang, Nagari Bayur, Nagari Koto Malintang and Nagari Maninjau. Keywords (key word): Review, Land Use, Economy, Vulnerability.